The Fiscal and Monetary Linkage between Stock Returns and Inflation - GESKE, ROBERT; ROLL, RICHARD (Journal of Finance, 1983)
ABSTRACT Contrary to economic theory and common sense, stock returns are negatively related to both expected and unexpected inflation. We argue that this puzzling empirical phenomenon does not indicate causality. Instead, stock returns are negatively related to contemporaneous changes in expected inflation because they signal a chain of events which results in a higher rate of monetary expansion. Exogenous shocks in real output, signalled by the stock market, induce changes in tax revenue, in the deficit, in Treasury borrowing and in Federal Reserve “monetization” of the increased debt. Rational bond and stock market investors realize this will happen. They adjust prices (and interest rates) accordingly and without delay. Although expected inflation seems to have a negative effect on subsequent stock returns, this could be an empirical illusion, since a spurious causality is induced by a combination of: (a) a reversed adaptive inflation expectations model and (b) a reversed money growth/stock returns model. If the real interest rate is not a constant, using nominal interest proxies for expected inflation is dangerous, since small changes in real rates can cause large and opposite percentage changes in stock prices.